Given:
f(x)= x + 3x^2 - 25
Rewrite:
f(x)= 3x^2 + x - 25
a= 3
b= 1
c= -25
Apply the Quadratic formula:
![\frac{-b\pm\sqrt[\placeholder{⬚}]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/ut8iy9v7nby7vdgeom4hmkldwlf25huj4e.png)
Replacing:
![\frac{-1\pm\sqrt[\placeholder{⬚}]{1^2-4(3)(-25)}}{2(3)}](https://img.qammunity.org/2023/formulas/mathematics/college/4z6xpsarwei0ohiz50i2s47uja07ory95s.png)
![\frac{-1\pm\sqrt[\placeholder{⬚}]{301}}{6}](https://img.qammunity.org/2023/formulas/mathematics/college/529ogq32gcx72sumvzjtmx5l6ch1sn6eus.png)
positive:
-1+√301 / 6 = 2.72
negative
-1-√301 / 6 = -3.06
Intercepts ( 2.72 , 0 ) (-3.06,0)
There are no asymptotes because it is not a rational function
Graph: